Evaluation of the antioxidant activity of Thymbra capitata, Thymus mastichina and Thymus camphoratus essential oils - Miguel, Maria Graça (2015)
The essential oils of Thymbra capitata, Thymus mastichina and Thymus camphoratus, collected during the vegetative phase, were predominantly composed of oxygen-containing monoterpenes (61-76%). Carvacrol was the dominant component of T. capitata oil (72%), 1,8-cineole (49%) dominated that of Th. mastichina, and linalool (17%), linalyl acetate (15%) and 1,8-cineole (11%) dominated Th. camphoratus oil. The essential oils and butylated hydroxyanisole (BHA) showed weakfree radical scavenging ability in peanut oil when compared to butylated hydroxytoluene (BHT). In sunflower oil, both the essential oils and the synthetic antioxidants exhibited relatively low free radical scavenging ability. Significant differences in the acid value were detected after several days' storage. From day 55 of storage until the end of the experiment, the acid value for both peanut and sunflower oil with added essential oils was similar and significantly lower than that of the control, but significantly higher than those with added BHA and BHT.